Global research landscape of telomere biology in infectious diseases: mechanistic links between host–pathogen interactions and immune ageing - Wakai, Theophilus Nang; Yensii, Nina Ghislaine; Kernyuy, Fabrice Banadzem; Bella-Omunagbe, Mercy; Chinedu, Shalom Nwodo; Afolabi, Israel Sunmola (Frontiers in Aging, 2026)
Telomeres, nucleoprotein structures located at the ends of chromosomes, maintain genomic stability and regulate cellular lifespan, particularly in immune cells. Telomere shortening, driven by cell division and limited telomerase activity, accelerates immune ageing and increases susceptibility to infectious diseases. Chronic infections like HIV and tuberculosis exacerbate telomere attrition through sustained immune activation and oxidative stress. This study presents a bibliometric review of research on telomere length and infectious diseases from 2005 to 2025. Data from the Web of Science Core Collection were analysed using VOSviewer and CiteSpace, software tools for visualising co-authorship, citation, and keyword networks, to assess publication trends, collaborations, and themes. A total of 123 publications were identified, showing steady growth with a 60% increase in publications from 2020 to 2022 during the COVID-19 pandemic. Leading journals included Frontiers in Immunology, PLoS ONE, and Scientific Reports. The United States produced the largest share of publications, followed by Canada and Spain, with notable contributions from the University of British Columbia and Université de Montréal. Influential authors such as Côté HCF, Pick N, and Maan EJ have advanced research, particularly in the areas of HIV and tuberculosis. Keyword analysis highlighted two dominant themes: immune ageing and infection-related stress. Malaria research was comparatively scarce, underscoring a gap for future investigation. These findings inform future research on telomere-targeted interventions and epidemiological studies aimed at enhancing infectious disease management. This review provides a comprehensive overview of the field’s progress and identifies key areas for future investigation.